The heuristic for mark planning process in a context of mass customization production - puasakul, kritsada (Naresuan University Engineering Journal, 2017)
Nowadays, garment manufacturers encounter with three major changes which are a progress in communication technology, an occurrence of efficient transportations, and a rapid change in customer requirement. To cope with these three changes, a mass customization production strategy is applied. However, to successfully use such flexible strategy, garment manufacturers should reduce their work-in-process inventory workloads. To include this workload, a sewing schedule is incorporated to reflect a sewing sequence in an assembly line. The purpose of this paper is to develop a heuristic approach that is used to improve a marking plan with respect to a work-in-process inventory workload. A key concept used to develop a heuristic is to rearrange marker patterns of all markers in order to reduce differences among due dates in each marker. Furthermore, this heuristic is divided into two steps, i.e. marker pattern rearrangement and stack rearrangement. To evaluate a performance, 140 problem instances generated based on a major characteristic of a mass customization are tested. Subsequently, all solutions are compared with solutions derived from a Genetic Algorithm based approach which is modified especially for this problem. Compared results show that solutions from the heuristic are better than solutions from a Genetic Algorithm method in 132 problem instances which is equal to 94.3%. Finally, it can be concluded that the heuristic is superior to a genetic algorithm method.